Periodontitis and its associated factors in patients at the faculty of southern Brazil: a cross-sectional study - Ghion, Fabiane; Dotto, Lara; Onofre, Rafael Sarkis; Rigo, Lilian (Acta Scientiarum. Health Sciences, 2022)
To verify the presence of periodontitis, its severity, and their association with associated factors based on medical records of patients who attended the Dental Clinic of the Faculty of Southern Brazil over 4 years. This is a cross-sectional study, which included 422 medical records of patients aged ≥ 18 years. The clinically analyzed data were: plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL). Sociodemographic data, dental hygiene, harmful habits and chronic systemic diseases were described. Statistical analysis of binary logistic regression was used to verify the relationship between the severity of periodontitis and the exposure variables. The older adults [odds ratio (OR) = 2.36; 95% confidence interval (CI): 1.23-4.54 – 41 to 55 years and OR = 3.0; 95% CI: 1.49-6.09 – 56 to 87 years], and men (OR = 1.9; 95% CI: 1.18-3.14) showed higher chances of periodontitis severity. Smokers (OR = 3.54; 95% CI: 2.05-6.12), those with hypertension (OR = 2.11; 95% CI: 1.23-3.63) and with diabetes (OR = 2.10; 95% CI: 1.08-4.12) showed higher chances of developing advanced periodontitis. Advanced or severe periodontitis occurred in one-third of the patients. The findings showed that men, older adults, with systemic arterial hypertension, diabetes mellitus, and smokers are more susceptible to severe periodontitis.